Case Studies of Geothermal System Response to Perturbations in Groundwater Flow and Thermal Regimes. Issue 2 (18th March 2021) - Abesser, Corinna; Schincariol, Robert A.; Raymond, Jasmin; García‐Gil, Alejandro; Drysdale, Ronan; Piatek, Alex; Giordano, Nicolò; Jaziri, Nehed; Molson, John
Abstract: Global demands for energy‐efficient heating and cooling systems coupled with rising commitments toward net zero emissions is resulting in wide deployment of shallow geothermal systems, typically installed to a depth of 100 to 200 m, and in the continued growth of the global ground source heat pump (GSHP) market. Ground coupled heat pump (GCHP) systems take up to 85% of the global GSHP market. With increasing deployment of GCHP systems in urban areas coping with limited regulations, there is growing potential and risk for these systems to impact the subsurface thermal regime and to interact with each other or with nearby heat‐sensitive subsurface infrastructure. In this paper, we present three numerical modeling case studies, from the UK and Canada, which examine GCHP systems' response to perturbation of the wider hydrogeological and thermal regimes. The studies demonstrate how GCHP systems can be impacted by external influences and perturbations arising from subsurface activities that change the thermal and hydraulic regimes in the area surrounding these systems. Additional subsurface heat loads near existing schemes are found to have varied impacts on system efficiency with reduction ranging from <1% to 8%, while changes in groundwater flow rates (due to a nearby groundwater abstraction) reduced the effective thermal conductivity at the study site by 13%. The findings support the argument in favor of regulation of GCHP systems or, to a minimum, their registration with records of locations and approximate heat pump capacity—even though these systems do not abstract/inject groundwater.